Effects of concurrent training on speed and agility performance in soccer referees - Baydemir, Barış; Kaçay, Zülbiye; Talaghir, Laurentiu-Gabriel; Ivan, Paula (Frontiers in Physiology, 2026)
PurposeSoccer referees are exposed to high aerobic and anaerobic demands during match play, yet evidence regarding training strategies that simultaneously enhance speed and agility in this population remains limited. This study aimed to examine the effects of a 12-week concurrent training program on sprint and agility performance in soccer referees and to evaluate the sustainability of these effects through a follow-up assessment. To our knowledge, few intervention studies have simultaneously examined both sprint speed and agility performance in soccer referees and evaluated whether these adaptations are retained during a follow-up period. Importantly, the inclusion of a follow-up assessment provides evidence on the retention of training-induced adaptations, which has rarely been examined in referee populations under applied field-based training conditions.MethodsFifty male soccer referees officiating in amateur leagues were assigned to a control group (n = 25) or an experimental group (n = 25). Both groups completed standard referee training twice weekly for 12 weeks, while the experimental group additionally performed concurrent training sessions combining endurance-based interval running and strength–power exercises twice per week. Sprint and agility performance were assessed using the 100 m sprint test and the Illinois Agility Test at pre-test, post-test, and 7-week follow-up. Data were analyzed using two-way mixed repeated measures ANOVA.ResultsSignificant Group × Time interaction effects were observed for both sprint and agility performance (p < 0.01) with moderate-to-large interaction effects. The experimental group demonstrated greater improvements in 100 m sprint and Illinois Agility Test performance compared with the control group following the intervention. Importantly, these performance gains were largely maintained at follow-up, indicating sustained training adaptations.ConclusionA 12-week concurrent training program integrated into standard referee conditioning resulted in significant and sustained improvements in speed and agility performance. These findings highlight the effectiveness of concurrent training as a multidimensional approach to enhancing physical capacities that are critical for soccer refereeing and support its practical implementation within referee training programs. These results support the integration of concurrent training into referee conditioning programs to improve movement efficiency and match positioning capacity. Practitioners may consider concurrent training as a feasible strategy to improve and maintain key physical qualities required for match positioning across competitive phases.